Using formal methods to scope performance challenges for Smart Manufacturing Systems: Focus on agility. (December 2015) - Jung, Kiwook; Morris, KC; Lyons, Kevin W; Leong, Swee; Cho, Hyunbo
Smart Manufacturing Systems need to be agile to adapt to new situations by using detailed, precise, and appropriate data for intelligent decision-making. The intricacy of the relationship of strategic goals with operational performance across the many levels of a manufacturing system inhibits the realization of Smart Manufacturing Systems. This article proposes a method for identifying what aspects of a manufacturing system should be addressed to respond to changing strategic goals. The method uses standard modeling techniques in specifying a manufacturing system and the relationship between strategic goals and operational performance metrics. Two existing reference models related to manufacturing operations are represented formally and harmonized to support the proposed method. The method is illustrated for a single scenario using agility as a strategic goal.